Imides : medicinal, agricultural, synthetic applications and natural products chemistry - Luzzio, Frederick A. (Developments in organic chemistry., 2019)
Imides: Medicinal, Agricultural, Synthetic Applications and Natural Products Chemistry provides a comprehensive overview of imides being developed as pharmaceuticals or experimental therapeutics. Featuring a diverse range of experts in the field of imides, each chapter reviews the state-of-the-art, including the isolation and identification of naturally-occurring imides, as well as the total synthesis of imide natural products. As there is a need for a comprehensive review of imides as a class of naturally-occurring, biologically active molecules, this book will be invaluable to those in pharmaceuticals, academia, and anyone looking for clinical applications.